Whole Exome Sequencing Identifies Rare Protein‐Coding Variants in Behçet's Disease. Issue 5 (May 2016) - Ognenovski, Mikhail; Renauer, Paul; Gensterblum, Elizabeth; Kötter, Ina; Xenitidis, Theodoros; Henes, Jörg C.; Casali, Bruno; Salvarani, Carlo; Direskeneli, Haner; Kaufman, Kenneth M.; Sawalha, Amr H.
Abstract : Objective: Behçet's disease (BD) is a systemic inflammatory disease with an incompletely understood etiology. Despite the identification of multiple common genetic variants associated with BD, rare genetic variants have been less explored. We undertook this study to investigate the role of rare variants in BD by performing whole exome sequencing in BD patients of European descent. Methods: Whole exome sequencing was performed in a discovery set comprising 14 German BD patients of European descent. For replication and validation, Sanger sequencing and Sequenom genotyping were performed in the discovery set and in 2 additional independent sets of 49 German BD patients and 129 Italian BD patients of European descent. Genetic association analysis was then performed in BD patients and 503 controls of European descent. Functional effects of associated genetic variants were assessed using bioinformatic approaches. Results: Using whole exome sequencing, we identified 77 rare variants (in 74 genes) with predicted protein‐damaging effects in BD. These variants were genotyped in 2 additional patient sets and then analyzed to reveal significant associations with BD at 2 genetic variants detected in all 3 patient sets that remained significant after Bonferroni correction. We detected genetic association between BD and LIMK2 (rs149034313), involved in regulating cytoskeletal reorganization, and between BD and NEIL1 (rs5745908), involved in base excision DNA repair ( P  = 3.22 × 10 −4 and P  = 5.16 × 10 −4, respectively). The LIMK2 association is a missense variant with predicted protein damage that may influence functional interactions with proteins involved in cytoskeletal regulation by Rho GTPase, inflammation mediated by chemokine and cytokine signaling pathways, T cell activation, and angiogenesis (Bonferroni‐corrected P  = 5.63 × 10 −14, P  = 7.29 × 10 −6, P  = 1.15 × 10 −5, and P  = 6.40 × 10 −3, respectively). The genetic association in NEIL1 is a predicted splice donor variant that may introduce a deleterious intron retention and result in a noncoding transcript variant. Conclusion: We used whole exome sequencing in BD for the first time and identified 2 rare putative protein‐damaging genetic variants associated with this disease. These genetic variants might influence cytoskeletal regulation and DNA repair mechanisms in BD and might provide further insight into increased leukocyte tissue infiltration and the role of oxidative stress in BD.